The Influence of Professional Training and Auditor Experience on Auditor Performance at Public Accounting Firms - Harukmi, Anggun Pramesthi; Rahman, Arief (Jurnal Aplikasi Bisnis, 2025)
This research paper aims to analyze the influence of professional training and auditor experience factors on auditor performance. Using a quantitative method with PLS-SEM (Partial Least Squares – Structural Equation Modeling) which carried out using SmartPLS 4.0 software. Furthermore, the data source used in this research is primary data, using questionnaires. The minimum sample collection method was measured using the Hair sampling method. An online questionnaire was conducted, and there were 135 respondents who had worked or were currently working as auditors at a Public Accounting Firm, who were used as the sample of this research. The results of this research show that the professional training and auditor experience have a positive effect on auditor performance. The research is valuable for researchers to understand the influence of professional training and auditor experience on auditor performance. Furthermore, the results of this research can be a source of ideas and input for further research.